LRT DC electrification project : part I : GTO technology in the DC chopper controlled motors : simulation work - 242647 Lau, Kin Fatt (Kuala Lumpur : UTM, 1995)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1995